A complementary note for the analytical method to estimate individual attention fluctuation using steady-state evoked potentials. (March 2023) - Norouzpour, Amir; Roberts, Tawna L.; Klein, Stanley A.
Abstract: Intra-individual variability of steady-state evoked potentials (ssEPs) is correlated with attention fluctuations and reveals the participant's ability to sustain attention. We previously presented an analytical method to measure the variation of discrete Fourier measurements at the frequency of interest extracted from ssEP data and to model the Fourier estimates on the two-dimensional complex plane with an ellipse. In this paper, we will introduce the ratio of the major to minor axes of the ellipse, which we call the Length-to-Width Ratio (LWR), as an index of individual ability to control attention and show how to calculate the confidence interval of the LWR to be able to compare the LWR between conditions within a participant as well as between participants within or between studies. The method will enable us to find out the most sensitive electroencephalography electrode to attention fluctuation, to explore the neural correlates of attention, to differentiate cases with inconsistent control of attention from normal participants, and to objectively monitor the effects of therapeutic interventions on attention.